Powder-bed-based 3D printing with cement for sustainable casting - Seung-Yeop Chun; Su-jin Kim; Woon-Gi Kim; Geumyeon Lee; Myeung-jin Lee; Bora Ye; Hong-Dae Kim; Jeong Hun Lee; Taewook Kim (Journal of Materials Research and Technology, 2023)
3D printing allows for the cost-effective fabrication of moulds and can cast complex shapes. In this study, alumina cement and fine aggregates for refractories were used as the main raw materials, and saturation was adjusted to an appropriate level to control the cement binder mixture for sand casting. For cast iron, the mould must withstand temperatures of up to 1400 °C and must exhibit sufficient strength, gas permeability, and thermochemical durability at high temperatures. To accomplish these requirements, 3D printing powder was prepared by adjusting the ratio of fine aggregate (D50: 30 μm) and an even finer cement component (D50: 4 μm). To improve the moulding quality, a green body was used to optimise the cement admixtures to increase the strength, and the saturation level of the 3D printer was adjusted for dimensional accuracy. The high-temperature durability of the mould was evaluated by measuring its strength after heat treatment, using Simultaneous Thermal Analysis (TG-DSC), and through dimensional stability assessment. In addition, the pores of the specimens were analysed through microscale X-ray tomography. The surface resolution and tolerance of the final casting were determined by a 3D image roughness test using a surface roughness scanner. The cement exhibited the shortest curing time and the highest strength when the mass ratio of CA (CaO·Al2O3) to C12A7 (12CaO·7Al2O3) was 8:2. The final mixing mass ratio of cement to the fine aggregate was 8:2, which was determined based on the relationship between flowability and powder bed surface quality. The results proved the high-temperature thermal stability of the 3D-printed mould, which showed a total mass reduction of less than 3% and a low coefficient of linear expansion up to 1300 °C. Consequently, the suitability of the 3D-printed moulded body, composed of casting sand with cement as a binder, for casting at temperatures >1400 °C was demonstrated. Additionally, the final printed porous mould de-powdered easily, and its recyclability was verified by strength testing various mass ratios of fresh and recycled powder. Therefore, through optimisation of the material combinations and adjustment of the 3D printing process parameters, optimal gas permeability and moulding resolution could be achieved without any casting defect, while maintaining handling strength. The findings of this study demonstrate the potential of expanding the scope of powder-bed-based 3D printing of cement material to the casting market.